The Influence of Platform Ease of Use, IT Infrastructure Quality and Digital Training Effectiveness on the Digital Employee Experience of Human Resources Department Employees - Sidjabat, Sonya; Purwati, Sri; Anantadjaya, Samuel PD; Nawangwulan, Irma M; Tawil, Muhamad Risal; Sonani, Nia (Journal of Information System, Technology and Engineering, 2026)
Organizations need to establish a suitable digital employee experience platform which enables their employees to work effectively while maintaining high productivity levels to achieve their digital transformation goals in Human Resources. This study examines how platform usability and IT system performance and digital training methods together influence the digital work experience of Human Resources Department employees. The researchers used a quantitative research approach that employed an explanatory framework to conduct their investigation. The researchers obtained data by conducting a survey to 160 participants who were selected through purposive sampling. The researchers conducted data analysis through multiple linear regression after they validated and verified reliability and classical assumption testing. The results demonstrated that platform usability together with IT system performance and digital training methods created a positive impact on the digital work experience. The study shows that three elements create an effective digital work environment because users need a system that they can easily operate while technological systems must function reliably and digital training programs must succeed in their execution. The study findings offer organizations practical guidance to create digital HR systems which enhance employee satisfaction and productivity.